Baseline electrolyte abnormalities would be related to poor prognosis in hospitalized coronavirus disease 2019 patients. (September 2020) - Tezcan, M.E.; Dogan Gokce, G.; Sen, N.; Zorlutuna Kaymak, N.; Ozer, R.S.
Abstract: Electrolyte abnormalities are not uncommon in coronavirus disease 2019 (COVID-19). Several studies have suggested that various electrolyte imbalances seem to have an impact on disease prognosis. However, no study has primarily focused on the effect of baseline electrolyte abnormalities on disease outcome. In this study, we assessed the validity of the hypothesis that baseline electrolyte imbalances may be related to unfavourable outcomes in hospitalized COVID-19 patients. Design of the study was retrospective and observational. We included 408 hospitalized individuals with COVID-19 over 18 years old. Baseline levels of sodium, potassium, calcium and chloride were assessed and the effects of abnormalities in these electrolytes on requirement for intensive care unit and mechanical ventilation, hospitalization duration and treatment outcome were evaluated. Patients were clustered based on electrolyte levels and clusters were compared according to outcome variables. Frequency of other severe disease indices was compared between the clusters. Lastly, we evaluated the independent factors related to COVID-19-associated deaths with multivariate analyses. In all, 228 (55.8%) of the patients had at least one electrolyte imbalance at baseline. Hyponatraemia was the most frequent electrolyte abnormality. Patients with hyponatraemia, hypochloraemia or hypocalcaemia had, respectively, more frequent requirement for intensive care unit and mechanical ventilation, higher mortality rate and longer hospitalization. The clusters associated with electrolyte abnormalities had unfavourable outcomes. Also, Clinical and laboratory features associated with severe disease were detected more often in those clusters. Hyponatraemia was an independent factor related to death from COVID-19 (OR 10.33; 95% CI 1.62–65.62; p 0.01). Furthermore, baseline electrolyte imbalances, primarily hyponatraemia, were related to poor prognosis in COVID-19 and baseline electrolyte assessment would be beneficial for evaluating the risk of severe COVID-19. Highlights: More than half of the hospitalized COVID-19 patients had electrolyte abnormalities. Hyponatraemia was the most frequent electrolyte anomaly. Hyponatraemia, hypochloraemia and hypocalcaemia were related to unfavorable outcomes in COVID-19 patients. Hyponatraemia is one of the independent factors related to death from COVID-19.